News Framing of the Free Nutritious Meal Program in IDN Times and Kompas.id: A Robert Entman Analysis - Doni Hermawan; Iskandar Zullkarnain; Lusiana Andriani Lubis (UMSU, 2026)
The Free Nutritious Meal Program (MBG) is one of the priority policies of Prabowo Subianto’s administration, aimed at improving the nutritional quality of the population and reducing stunting rates in Indonesia. In its implementation, this program has generated various responses, ranging from appreciation for its socio-economic benefits to criticism regarding food poisoning cases, budget governance, and technical issues in its implementation. This study aims to analyze the construction of reality of the MBG Program in the online news coverage of IDN Times and Kompas.id and to compare the framing characteristics used by the two media outlets. This research employs a constructivist paradigm with a qualitative approach. The data were obtained through documentation of ten news articles selected purposively from January 2025 to January 2026 and were strengthened through interviews with the editorial teams of both media outlets as source triangulation. The data were analyzed using Robert N. Entman’s framing model, which includes define problems, diagnose causes, make moral judgment, and treatment recommendation, supported by the theory of social construction of reality, Hierarchy of Influences theory, mass communication theory, and new media theory. The findings show that IDN Times tends to frame the MBG program critically by highlighting issues of implementation, social impact, and government accountability, while Kompas.id places greater emphasis on balanced policy journalism through context, data, solutions, and program evaluation. These framing differences indicate that the media act as agents of reality construction in shaping public understanding of government policies